CONDUCTIVITY STRUCTURE OF THE UPPER MANTLE IN AN ACTIVE SUBDUCTION ZONE - Semenov V.Y.; Rodkin M. (My University, 1996)
The results of deep electromagnetic soundings for the active transition ocean-continent zone at Sakhalin Island are presented. After an averaging procedure of the magnetotelluric response functions, the period range was extended up to 500 days by using the geomagnetic soundings of the Yuzhno-Sakhalinsk, Kakioka and Memambetsu observatory data. The existence of the asthenosphere and a high conductivity layer located at the base of the upper mantle was established by one-dimensional inverse methods. High resistivity revealed at depths of 250-450 km appears to be connected with the penetration of the cold slab into the mantle. The possible nature of a mid-mantle conductive layer and the relation of its conductances with the tectonic history are discussed.